Male and Female Portraits in Russian Proverbs: Status of Husbands and Wives - Aroonoast, Parit (Journal of Letters, 2025)
This research article studied the portrayal of husbands and wives in Russian proverbs to analyze the thoughts and beliefs of Russians on gender roles from Christian perspectives and the concept of hegemonic masculinity. Data was collected from Vladimir Dal’s “Proverbs of the Russian People” (1879), one of the largest collections of Russian proverbs. The literature indicates that Russian proverbs tend to be misogynistic, reflecting societal domination by hegemonic masculinity. Men were seen as leaders before the adoption of Christianity in Russia, but Russian proverbs influenced by Christian teachings imply that hegemonic masculinity opposes biblical teachings. Despite different spousal responsibilities, the emphasis is on mutual love, respect, and honor. This approach promotes a family life of reciprocal support, rather than gender inequality, as considered and interpreted in the patriarchal society framework.